Impact of drought tolerant maize adoption on maize productivity, sales and consumption in rural Zimbabwe. Issue 1 (2nd January 2017) - Makate, Clifton; Wang, Rongchang; Makate, Marshall; Mango, Nelson
ABSTRACT: Increased frequency of droughts (especially mid-season dry spells), higher than normal temperatures and altered patterns of precipitation and intensity are some of the extreme weather events evident in southern Africa. These extreme weather events present a threat to livelihoods and sustainability of agricultural production in the region. However, several climate-smart agricultural technologies (including drought-tolerant maize) believed to offer adaptation to climate variability in maize-based farming systems have been widely adopted. Moreover, empirical work on these technologies is limited. This paper demonstrates how by adopting drought-tolerant maize, a climate-smart agricultural technology impacts on the quantities of maize produced, sold and consumed in Zimbabwe. Using primary data on smallholder farmers collected in 2011 in Zimbabwe's four districts, we employed propensity score matching techniques to construct a suitable comparison group and calculate the average treatment effect on the treated sample. We find that, the adoption of drought-tolerant maize (DTM) in rural Zimbabwe significantly enhances overall maize productivity and consequently the quantities set aside for sale and personal household consumption. Our study therefore suggests that, systematic expansion of climate-smart agricultural technologies such as adoption of drought-tolerant maize can significantly improve maize yields, sales and consumption in rural Zimbabwe. Our empirical results, robust to sensitivity checks, strongly point to the overall importance of DTM adoption in Zimbabwe. The findings from this paper also have very important implications for overall efforts on the promotion of climate-smart agriculture technologies in Africa and other developing countries.